Different types of parental stress and childhood obesity: A systematic review of observational studies. (1st September 2019) - Jang, Myoungock; Owen, Brenda; Lauver, Diane R.
Summary: Different types of parental stress may influence children's health behaviors and weight. The aim of this review was to systematically examine the relationships between parental stress and child obesity. We reviewed 27 studies published through December 2018 and classified parental stress as parents' general stress, parenting role stress, and life event stress. There were positive relationships of parents' general stress and parenting role stress with child obesity among families with younger children and in longitudinal studies. The relationship between life event stress and child obesity differed by measures. We found that parenting role stress may be associated with unhealthy parenting practices. Contextual factors such as children's and parents' sex, race or ethnicity, socioeconomic status, and family structure appeared to play a moderating role in the relationship between parents' stress and child obesity, which warrant cautious interpretation. Our recommendations for future research include clarifying further the types of parental stress that influence child obesity, evaluating long‐term relationship between parental stress and child obesity, and identifying possible mediating factors to support the relationship between parents' stress and child obesity. Researchers may also consider developing stress management programs for parents to address child obesity.